A new vision measurement method based on active object gazing. (6th July 2017) - Xu, De; Wang, Qingbin
A new vision measurement system is developed with two cameras. One is fixed in pose to serve as a monitor camera. It finds and tracks objects in image space. The other is actively rotated to track the object in Cartesian space, working as an active object-gazing camera. The intrinsic parameters of the monitor camera are calibrated. The view angle corresponding to the object is calculated from the object's image coordinates and the camera's intrinsic parameters. The rotation angle of the object-gazing camera is measured with an encoder. The object's depth is computed with the rotation angle and the view angle. Then the object's three-dimensional position is obtained with its depth and normalized imaging coordinates. The error analysis is provided to assess the measurement accuracy. The experimental results verify the effectiveness of the proposed vision system and measurement method.